Perancangan Prototipe Business Intelligence Dashboard Penjualan PT ABC - Goh, Bryan Jordan; Trisnawarman, Dedi (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
In a competitive business era, efficient and informative sales data management is essential for company success. The purpose of developing this sales dashboard prototype is to monitor sales data, integrate data from various sources, and make smarter business decisions. PT ABC, as a company engaged in milk sales, realizes the importance of timely monitoring of sales data and accurate analysis. The method used in the development of the dashboard is the SDLC prototyping method. The initial stages include needs identification, then design, followed by the creation of an initial prototype that is used to get feedback from stakeholders. The prototype will be designed using Power BI tools then the prototype results will be improved based on feedback. Through this design, the needs of decision makers will be better understood. The result of the design is sales data visualization based on Key Performance Indicators, namely sales targets and sales growth.